2018
DOI: 10.12691/ajmr-6-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Mycological and Mycotoxins Analysis of Kareish and Soft Cheese in Assiut, Egypt

Abstract: During the present study 80 samples of kareish (semi-soft cheese with 20% fats) and soft cheese (40 % fats) were collected Assiut City during June to December 2015. The fungal content of these samples was evaluated using Dichloran Rose Bengal Chloramphenicol (DRBC) and Yeast Extract Malt extract (YM) agar media. The fungal count per sample ranged from 7 colonies/g in soft cheese to 44800 colonies/g in kareish cheese. the total number of fungal species in kareish cheese was slightly lower on DRBC than on YM (24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…from Akawi cheese. Aspergillus was reported in other types of Egyptian white cheeses; Moharram et al (2018) reported existence of A. carneus, A. flavus, A. fumigatus, A. niger, A. nidulans, A. sulphureus, A. sydowii and A. terreus in soft cheese.…”
Section: Aspergillus In Egyptmentioning
confidence: 93%
See 1 more Smart Citation
“…from Akawi cheese. Aspergillus was reported in other types of Egyptian white cheeses; Moharram et al (2018) reported existence of A. carneus, A. flavus, A. fumigatus, A. niger, A. nidulans, A. sulphureus, A. sydowii and A. terreus in soft cheese.…”
Section: Aspergillus In Egyptmentioning
confidence: 93%
“…Various species of Aspergillus were reported to recover from Karish cheese samples such as; A. flavus (El-Diasty and Salem 2007;Younis et al 2016;Moharram et al 2018;Moubasher et al 2018c), A. fumigatus (ELbagory et al 2014Hameed 2016;Moharram et al 2018), A. niger (El-Diasty andSalem 2007;Hameed 2016;Younis et al 2016;Moharram et al 2018;Moubasher et al 2018c), A. nidulans (Moharram et al 2018) andA. terreus (ELbagory et al 2014;Hameed 2016;Moharram et al 2018).…”
Section: Aspergillus In Egyptmentioning
confidence: 99%